The Correlation Between Students’ Emotional Intelligence and Public Speaking Performance at State Senior High School 1 Mungka - Firdaus, Firdaus; Irwandi, Irwandi; Eliza, Eliza; Safitri, Loli (Journal of English Language and Education, 2026)
Emotional factors are often considered crucial in influencing students’ success in English speaking activities, particularly in public speaking contexts. Emotional intelligence plays an important role in supporting students’ confidence and effectiveness in public speaking activities. This study aimed to examine the relationship between students’ emotional intelligence and their public speaking performance in English presentations. This research employed a quantitative correlational design involving 25 twelfth-grade students at SMAN 1 Mungka who were selected using total sampling. Data were collected through an emotional intelligence questionnaire and documentation of students’ public speaking performance scores. The questionnaire was validated using Aiken’s V through expert judgment and demonstrated acceptable reliability based on Cronbach’s Alpha. The data were analyzed using descriptive statistics and Pearson correlation analysis with the help of SPSS. The findings revealed that students generally showed a good level of emotional intelligence and moderate public speaking performance. The correlation analysis indicated a very strong and significant positive relationship between emotional intelligence and public speaking performance (r = 0.956, p 0.01). These results suggest that emotional intelligence contributes to students’ success in delivering English presentations.